Pengembangan Bahan Ajar Brosur Berdasarkan Hasil Analisis Morfometrik Jenis Ikan Hasil Tangkapan Nelayan - Risna Wati Kasim; Sukardi Abbas; Juniartin Juniartin; Astuti Muh. Amin (IAIN Ternate, 2022)
Brochures can be used as interesting learning resources in classroom learning, because of their simple and practical form. There are many studies on fish analysis and morphometric analysis, but so far, researchers have not found any results related to the morphometric results of fish caught by fishermen in Dufa-dufa Village. The type of research used is qualitative research and then continued with Research and Development (R&D) research with a 4-D model. The population in this study were all types of fish caught by fishermen from Dufa-dufa Village on each ship. The sample in this study was each species of fish taken from the catches of fishermen in Dufa-dufa Village, where three fish samples were taken from each type of fish whose weight was not too much different from other fish. The data analysis technique used is morphometric data analysis and analysis of the validity of brochure teaching materials. Based on the measurement of the morphometric character of each fish, it shows that the one with the largest morphometric size is tuna in sample 3 of the catches of the fishermen group at PPI with an average total length of 39.7 cm and the smallest morphometric size is mackerel in sample 3 of the catches of fishermen. at Fishbone Beach with a total length of 16 cm. The validity of the Pisces morphometric material brochure that was developed shows the